On eating’s pleasure of women of low-income socioeconomic status in Petare, Caracas, Venezuela - Herrera Cuenca, Marianella (Anales Venezolanos de Nutrición, 2024)
Eating is a key biological, social, cultural, historical, geographical, agricultural, religious and hedonic act. Whether the pleasure on eating can be developed from scarcity might be controversial, as the development of taste involves the exposure to a variety of foods during critical periods of time and will be associated to what is available for the people in their daily lives. This study aimed to study the preferred foods and dishes, of women within low and very low-income settings in Caracas, Venezuela during the month of June 2022, the willingness to grow ingredients at home and/or community gardens and what would they cook if money restriction was not a problem. Interviews were implemented by focus group to 18 pregnant and lactating women and community workers (women) on soup kitchens established in two very low-income settings in Eastern Caracas, Venezuela, to fulfil the aims of this study, and to understand the characteristics of the preferences. In general, the results obtained show absence of traditional Venezuelan complex dishes that have been replaced by foods that are either basic in its components, have international references, and can be prepared with foods that people have access to, thus the culinary memoires of the future younger generations can be compromised as there is an absence of those in the imaginary and dreams of the family mothers and cooking volunteers whose dream is to enrich with animal protein a basic carbohydrate already available. Comer es un acto biológico, social, cultural, histórico, geográfico, agrícola, religioso y hedónico. El hecho que el placer de comer pueda desarrollarse a partir de la escasez es un tema controversial, ya que el desarrollo del gusto implica la exposición a una variedad de alimentos durante períodos críticos del desarrollo y estará asociado a lo que se encuentra disponible para las personas en su vida diaria. Esta investigación tuvo como objetivo estudiar los alimentos y platos preferidos de mujeres en entornos de bajos y muy bajos ingresos en Caracas, Venezuela durante el mes de junio de 2022, la disposición a cultivar ingredientes en huertos familiares y/o comunitarios y qué cocinarían si la restricción de dinero no fuese un problema. Se implementaron entrevistas mediante un grupo focal a 18 mujeres embarazadas y lactantes y trabajadoras comunitarias (mujeres) en comedores populares establecidos en dos entornos de muy bajos ingresos en el este de Caracas, Venezuela, para cumplir con los objetivos de este estudio y comprender las características de las preferencias de las mujeres. En general, los resultados obtenidos muestran la ausencia de platos complejos tradicionales venezolanos que han sido reemplazados por alimentos básicos en sus componentes, con referencias internacionales y que pueden ser preparados con alimentos baratos a los que la gente tiene acceso, sacrificando así las memorias culinarias del futuro que las generaciones más jóvenes pueden ver comprometidas por su ausencia en el imaginario y en los sueños de las madres de familia y de las voluntarias cocineras cuya fantasía es enriquecer con proteína animal un carbohidrato básico ya disponible.